Study of Organic Substance (Myrmecodia pendans) Extraction Using Soxhletation Method as an Organic Inhibitor - Rohmannudin, Tubagus Noor; Sulistijono, Sulistijono; Adiyaksa, Muhammad; Chusururi, Mochamad Alvan Mifta (IPTEK Journal of Proceedings Series, 2018)
Extract of natural substance is currently being developed as an organic inhibitor. Organic inhibitor can be used to inhibit corrosion rate of metallic material especially steel. The purpose of this study is to analyze the effectiveness of soxhletation extraction methods and the quality of inhibitor of Sarang Semut (Myrmecodia pendans) extract. The variations implemented in this research were the composition of the solvent-material and the content comparison of flavonoid compounds. Â The results of Sarang Semut (Myrmecodia pendans) extract inhibitor using soxhletation extraction method was observed qualitatively and quantitatively This research used soxhletation extraction method, simplicia Sarang Semut (Myrmecodia pendans) powder as the organic substance, and a mixture of acetone and distilled water as the solvent. Ratio variation of the solvent-substance composition used are 1:10, 1:15, and 1:20. Tests used in this study were Extract Parameters, FTIR, TLC and UV-Vis Spectrophotometry and weight loss. The highest yield was shown when using 1:10 ratio which was 13.943%, the total ash content and the lowest extracted water content shown at a ratio of 1:10 with amount of 4.26% and 4.2483%. FTIR test results indicated functional groups of flavonoids compounds and TLC test showed positive results of Flavonoid compounds which were characterized by blackish discoloration. The highest percentage of flavonoid compounds of 0.22025% found at the 1:10 ratio. The highest efficiency inhibition happened when weight loss testing showed 500ppm with the result of 84.3%.